The opioid crisis in Canada: a national perspective - Lisa, Belzak; Jessica, Halverson (Health Promotion and Chronic Disease Prevention in Canada : Research, Policy and Practice, 2018)
Introduction: This review provides a national summary of what is currently known about the Canadian opioid crisis with respect to opioid-related deaths and harms and potential risk factors as of December 2017. Methods: We reviewed all public-facing opioid-related surveillance or epidemiological reports published by provincial and territorial ministries of health and chief coroners’ or medical examiners’ offices. In addition, we reviewed publications from federal partners and reports and articles published prior to December 2017. We synthesized the evidence by comparing provincial and territorial opioid-related mortality and morbidity rates with the national rates to look for regional trends. Results: The opioid crisis has affected every region of the country, although some jurisdictions have been impacted more than others. As of 2016, apparent opioid-related deaths and hospitalization rates were highest in the western provinces of British Columbia and Alberta and in both Yukon and the Northwest Territories. Nationally, most apparent opioid-related deaths occurred among males; individuals between 30 and 39 years of age accounted for the greatest proportion. Current evidence suggests regional age and sex differences with respect to health outcomes, especially when synthetic opioids are involved. However, differences between data collection methods and reporting requirements may impact the interpretation and comparability of reported data. Conclusion: This report identifies gaps in evidence and areas for further investigation to improve our understanding of the national opioid crisis. The Public Health Agency of Canada will continue to work closely with the provinces, territories and national partners to further refine and standardize national data collection, conduct special studies and expand information-sharing to improve the evidence needed to inform public health action and prevent opioid-related deaths and harms.